SOME SOLUTIONS FOR THE SUSTAINABLE ECONOMIC DEVELOPMENT OF VIETNAMESE ISLANDS IN THE CONTEXT OF CLIMATE CHANGE - Thoa, Le Thi Kim (Vietnam Journal of Marine Science and Technology, 2016)
The islands play important roles in socio-economic development and security, defense of the country. However, these places are strongly affected by the impacts of climate change, island and marine environment and resources are degraded and polluted. As a result, the government has paid attention to policy making for socio-economic development in the coastal areas and islands as well as policy planning for environmental and resource management in the sea and islands. Despite these efforts, the island’s economic development is still very low. From my point of view, island’s economy need to be examined based on its ecological and social charateristics. This paper will concentrate on the study of the sustainable economic development in Vietnam’s islands in the context of climate change. Especially, this study will focus on the following issues: (1) The island’s characteristics in ecology and society; (2) The opportunities and obstacles for the island’s economic development under climate change impacts; (3) The status of island’s economic development in Vietnam; and (4) Proposing major solutions to strengthen the sustainable economic development of Vietnamese islands.